Articulating Science Education with the Sociology of Education: the significant contribution of Ana Maria Morais (Práxis Educativa, 2023)
This paper aims to pay tribute to Ana Maria Morais, coordinator of the ESSA Group (Sociological Studies of the Classroom Group) which was part of the Unit for Research and Development in Education and Training (UIDEF) of the Institute of Education of the University of Lisbon. This tribute intends to highlight her academic legacy, of great professional merit and intellectual rigor, with a vast body of work in the fields of science education and sociology of education. It is enhanced her crucial role on the development of a pioneering research centred on the interaction between science education and sociology of education having as conceptual support the theory of the English sociologist Basil Bernstein. It is also referred her important role while defending a science education centred on scientific quality and rigor and a conceptually demanding education for all students.Keywords: Sociology of Education. Science Education. Ana Maria Morais.